Sex differences in the reward deficit and somatic signs associated with precipitated nicotine withdrawal in rats. (1st December 2019) - Tan, Sijie; Xue, Song; Behnood-Rod, Azin; Chellian, Ranjithkumar; Wilson, Ryann; Knight, Parker; Panunzio, Stefany; Lyons, Hannah; Febo, Marcelo; Bruijnzeel, Adriaan W.
Abstract: Female smokers are more likely to relapse than male smokers, but little is known about sex differences in nicotine withdrawal. Therefore, male and female rats were prepared with minipumps that contained nicotine or saline and sex differences in precipitated and spontaneous nicotine withdrawal were investigated. The intracranial self-stimulation (ICSS) procedure was used to assess mood states. Elevations in brain reward thresholds reflect a deficit in reward function. Anxiety-like behavior was investigated after the acute nicotine withdrawal phase in a large open field and the elevated plus maze test. The nicotinic receptor antagonist mecamylamine elevated the brain reward thresholds of the nicotine-treated rats but did not affect those of the saline-treated control rats. A low dose of mecamylamine elevated the brain reward thresholds of the nicotine-treated male rats but not those of the females. Mecamylamine also precipitated more somatic withdrawal signs in the nicotine-treated male than female rats. Minipump removal elevated the brain reward thresholds of the nicotine-treated rats for about 36 h but did not affect those of the saline-treated rats. There was no sex difference in the reward deficit during spontaneous nicotine withdrawal. In addition, the nicotine-treated male and female rats did not display increased anxiety-like behavior three to four days after minipump removal. In conclusion, these studies suggest that relatively low doses of a nicotinic receptor antagonist induce a greater reward deficit and more somatic withdrawal signs in male than female rats, but there is no sex difference in the reward deficit during spontaneous withdrawal. Highlights: A low dose of mecamylamine precipitates nicotine withdrawal in males but not females. There is no sex difference in reward deficits during spontaneous nicotine withdrawal. The stage of the estrous cycle does not affect the brain reward threshold of rats. Chronic nicotine administration only increases locomotor activity in female rats. There is no increase in anxiety 3–4 days after cessation of nicotine administration.